2016
DOI: 10.1021/jacs.6b01170
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic B–N Dehydrogenation Using Frustrated Lewis Pairs: Evidence for a Chain-Growth Coupling Mechanism

Abstract: The catalytic dehydrogenation of ammonia- and amine-boranes by a dimethylxanthene-derived frustrated Lewis pair is described. Turnover is facilitated on a thermodynamic basis by the ready release of H2 from the weakly basic PPh2-containing system. In situ NMR studies and the isolation of intermediates from stoichiometric reactions support a mechanism initiated by B-H activation, followed by end-growth BN coupling involving the terminal NH bond of the bound BN fragment and a BH bond of the incoming borane monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 48 publications
4
80
0
2
Order By: Relevance
“…The most interesting thing about these molecules is that they are reactive, activating H 2 and other bonds heterolytically. Linked amine-borane units have so far been relatively rare in FLP chemistry, but they are known (39)(40)(41)(42). We were thus encouraged to study the interaction of our substituted COTs with H 2 .…”
Section: Sidewaysmentioning
confidence: 99%
“…The most interesting thing about these molecules is that they are reactive, activating H 2 and other bonds heterolytically. Linked amine-borane units have so far been relatively rare in FLP chemistry, but they are known (39)(40)(41)(42). We were thus encouraged to study the interaction of our substituted COTs with H 2 .…”
Section: Sidewaysmentioning
confidence: 99%
“…[31,32] As far as we can ascertain, this is the first example of as tructurally characterised Ga-keteniminate complex. [32] Conclusions The bulky trisalkylgallium, Ga(CH 2 SiMe 3 ) 3 ,h as been found to be av iable, effective Lewis acid for promoting small molecule activation when combined with as trong base such as 1,3-bis(tert-butyl)imidazol-2-ylidene (ItBu), thus furthere xpanding the versatility of frustrated Lewis pair chemistry.T he activation of carbonyl compounds can be achieved either by reduction of the C=Of unctionality affording zwitterionic compounds such as [ItBuCH 2 OGaR 3 ]( 1)b yf orming an ew CÀCb ond, or [{ItBuH} + {(Me 3 C 6 H 2 )C(CH 2 )OGaR 3 } À ]( 9)b yC ÀHb ond activation. [32] Conclusions The bulky trisalkylgallium, Ga(CH 2 SiMe 3 ) 3 ,h as been found to be av iable, effective Lewis acid for promoting small molecule activation when combined with as trong base such as 1,3-bis(tert-butyl)imidazol-2-ylidene (ItBu), thus furthere xpanding the versatility of frustrated Lewis pair chemistry.T he activation of carbonyl compounds can be achieved either by reduction of the C=Of unctionality affording zwitterionic compounds such as [ItBuCH 2 OGaR 3 ]( 1)b yf orming an ew CÀCb ond, or [{ItBuH} + {(Me 3 C 6 H 2 )C(CH 2 )OGaR 3 } À ]( 9)b yC ÀHb ond activation.…”
Section: Reactionswith Ketones: C4 Insertion Versus Càha Ctivationmentioning
confidence: 99%
“…An early study dealing with the reaction of an isolable NHSi with B(C 6 F 5 ) 3 revealed the formation of the respective silyleneborane Si II !B(III) adduct and its transformation into as ilylborane. [11] There is no phosphine-borane adduct formation even with less sterically hindered PPh 2 and P i Pr 2 group.T he unwanted adduct formation in the intermolecular systems and the ability of the 9,9-dimethylxanthene backbone to avoid adduct formation encouraged us to explore the chemistry of as ingle-component B III -a nd Si II -centered FLP.H erein we wish to report the synthesis and characterization of the first single-component NHSi borane LSi-R-BMes 2 1 with the 9,9dimethylxanthene spacer and its striking reactivity for small molecules activation. [9] Our group described the formation of azwitterionic NHSi-borane adduct from the reaction of aNHSi bearing a b-diketiminate-like ligand with B(C 6 F 5 ) 3 .…”
mentioning
confidence: 98%
“…Va riable-temperature 1 HNMR measurements show that the SiH 2 proton resonance signal at d = 4.92 ppm at 298 Kg ives as plitting into two doublets (d = 5.51 and 4.48 ppm) at 213 Kw ith the observation of ab road doublet 11 Br esonance at d = À15.4 ppm, indicating the presence of weak SiH···B interactions.Attempts to grow single-crystals of 5-H 2 were unsuccessful owing to its high solubility.I ts composition has been confirmed by high-resolution (HR) electrospray ionization (ESI) mass spectrometry,which shows the molecular ion peak at m/z 719.45593 (calcd 719.45625). According to 1 H, 29 Si DEPT,and 1 H-29 Si HMQC NMR spectroscopy,o nly the new silane-borane product L(H 2 )Si-R-BMes 2 (5-H 2 )c ould be obtained.…”
mentioning
confidence: 99%